Mohs surgery for the treatment of eccrine spiroadenoma: a case report - Gabriela Tomasi Batiston; Jessica Maksoud Oliveira; Pedro Matheus Benelli; Guilherme Bueno de Oliveira; João Roberto Antônio (Sociedade Brasileira de Dermatologia (SBD), 2024)
Eccrine spiradenoma is a rare benign epithelial neoplasm derived from the ductal and secretory portions of the eccrine sweat glands. It is characterized by slow growth and may, in some cases, undergo malignant transformation. This report describes a case involving a male patient with a painful, slow-growing lesion present for 3 years. The nodular, lobulated lesion was located on the left frontal region. Due to the left. On account of location, size, and vascularization of the lesion, as well as the need to preserve the facial musculature and ensure complete tumor removal of the tumor with minimal functional damage, Mohs surgery was chosen as the treatment technique.